Analisis Faktor-Faktor yang Mempengaruhi Pajak Penghasilan Badan Sebagai Indikator Manajemen Perencanaan Pajak pada Perusahaan Sektor Manufaktur di Bursa Efek Indonesia Tahun 2013-2017 - Petrus Petrus (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to analyse and find out 1) the effect of Profitability on the Effective Tax Rate 2) Inventory Intensity to the Effective Tax Rate 3) Capital Intensity to the Effective Tax Rate 4) Leverage to the Effective Tax Rate. The population in this study are manufacturing sector companies listed on the Indonesia Stock Exchange during the period 2013-2017. The sample used in this study is 52 companies in all industry sector of manufacturing as research subjects. The sampling technique used is the Panel Data Estimation Technique. Overall the results of this study are 1) The probability of influencing Effective Tax Rate has a significant negative direction on manufacturing companies on the Indonesia Stock Exchange in 2013-2017, 2) Inventory Intensity affects the Effective Tax Rate having a negative but not significant direction on manufacturing companies in the Exchange Indonesia Securities in 2013-2017, 3) Capital Intensity affects the Effective Tax Rate to have a positive but not significant direction in manufacturing companies on the Indonesia Stock Exchange in 2013-2017, 4) Leverage affects Effective Tax Rate has a negative but not significant direction in manufacturing companies on the Indonesia Stock Exchange in 2013-2017.